Neonatal Lupus Erythematosus-Beyond Conduction Defects - Prem Alva; Shrishail Kumbar; Ashvij Shriyan; Aswathy Rajan (Galenos Yayinevi, 2023)
Neonatal lupus erythematosus is an uncommon disease; frequently undiagnosed, produced by the transplacental passage of autoantibodies such as anti-Ro/SSA and anti-La/SSB. Here, we discuss a case of a preterm baby with intracardiac calcification and right ventricular dysfunction detected antenatally and managed successfully with steroid and intravenous immunoglobulins.